Affirmative Humanities - Domańska, Ewa (Dějiny – teorie – kritika, 2018)
The explorations presented in the article provide a brief outline of the larger affirmative humanities project. Following Rosi Braidotti’s ideas of affirmative ethics and politics, I propose an understanding of affirmative humanities as a way of moving away from a postmodernist interest in apocalypse, catastrophes, extinction, trauma, suffering, voids, silence and exclusion. I consider affirmative humanities to be a project that is future oriented, envisioning the future in more positive ways (which is not to say naive and unrealistic ways), while aiming to empower the subject (human and non-human, individual as well as collective) and looking for alternative forms of community.